2015
DOI: 10.15547/bjvm.822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two stunning methods on postmortem muscle pH and meat quality of common carp (Cyprinus carpio L.)

Abstract: Percussive and electrical stunning are the most promising methods in terms of rendering fish unconscious prior to slaughter. The aim of this study was to determine the effect of these two stunning methods on postmortem muscle changes and meat quality of common carps. The experimental fish were stunned either by percussion (Group 1) or by electrical current application (Group 2), both followed by immediate decapitation. Muscle pH was measured at different time intervals to assess the postmortem metabolic change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The lighter color, as discussed by the authors, was due to denaturation of muscle proteins and loss of fluids, which resulted in changes in the reflection of light from the meat surface. This statement was supported by a study of Daskalova and Pavlov (2015) which revealed that the lack of significant differences in ultimate pH and levels of liquid loss was further associated with similar L* values.…”
Section: Meat Colormentioning
confidence: 73%
“…The lighter color, as discussed by the authors, was due to denaturation of muscle proteins and loss of fluids, which resulted in changes in the reflection of light from the meat surface. This statement was supported by a study of Daskalova and Pavlov (2015) which revealed that the lack of significant differences in ultimate pH and levels of liquid loss was further associated with similar L* values.…”
Section: Meat Colormentioning
confidence: 73%
“…To provide fresh and safe common carp product of good quality, development and application of effective species-specific processes before, during and after slaughter are needed ( 2 ). For common carp, many studies that have investigated the pre-slaughter and slaughter processes emphasise the importance of reducing the stress for meat quality ( 3 5 ). One of the processes that can be included in the slaughter is bleeding, and for common carp this is most commonly achieved by cutting the gill arches or by direct gutting ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In studies by Daskalova and Pavlov [39] with Cyprinus carpio L. in Bulgaria and Daskalova [28] in a systematic review of several fish species from Europe to South America, the authors pointed out that pre-slaughtering and stunning methods significantly influenced both the texture and the water activity (Aw) of the fillets tested during the days of storage under refrigeration. The texture profile analysis is widely used to evaluate the instrumental texture of fish fillets.…”
Section: Discussionmentioning
confidence: 99%